A psychoeducational mental health promotion intervention in a comprehensive schools: Recognising problems and reducing stigma. (August 2021) - Onnela, Anna; Hurtig, Tuula; Ebeling, Hanna
Objective: Adolescence is a vulnerable age for emerging mental health problems, but also a time at which the foundations for a healthy lifestyle are established. Attitudes towards mental health problems and the ability to recognise them can be affected at this age. The aim of this study was to describe a psychoeducative intervention aimed at increasing knowledge of mental health problems and decreasing the stigma of mental health disorders among eighth-grade students in Finland. Design: Mixed-methods exploration of how a universal psychoeducation delivered in the classroom can affect attitudes towards, and recognition of, mental health disorders and how young people perceive the psychoeducation received. Setting: The study involved 162 eighth-grade students in two comprehensive schools in Finland. Method: The intervention consisted of four lessons on the topics of anxiety, eating disorders, conduct disorder, and depression and substance use. Results: Students in both the intervention and non-intervention groups recognised the symptoms of mental health disorders well before and after the intervention, and the intervention improved boys' ability to recognise conduct disorder. Following the intervention, students saw mental health disorders as real medical conditions. Students experienced the intervention as beneficial, increasing their knowledge, understanding and open-mindedness with regards to mental health. Conclusion: Mental health promotion interventions have the goal of increasing the ability of individuals to understand mental health issues and engage in self-care of mental health. Providing mental health promotion interventions to young people has the potential to increase knowledge and skills in maintaining a healthy lifestyle in adulthood.